Analisis Pengaruh Preloading Kombinasi Prefabricated Vertical Drain pada Proses Konsolidasi di Proyek Reklamasi di Samping Tangki Cpo Antar Pulau Belawan Berdasarkan Bore Log Bh-2) - Muhammad Fadhil Lubis; Roesyanto; Gina Cynthia Raphita Hasibuan (Syntax Corporation Indonesia, 2023)
To carry out construction on soft soil, cases of land subsidence are often encountered. This is due to the low bearing capacity and small shear force, large compression, and very small permeability. To address this problem, one method that can be implemented is soil improvement using preloading and Prefabricated Vertical Drain (PVD). The aim of this research is to find out the magnitude of consolidation settlement by using analytical methods and by using PLAXIS 2D modeling at reclamation project locations besides CPO tanks between Belawan Islands based on Bore Log BH-02 data. It is also to compare coarse mesh, medium mesh, and fine mesh in PLAXIS 2D modeling, and to obtain the amount of land subsidence using preloading only and preloading with a combination of preloading and Prefabricated Vertical Drain (PVD) based on Bore Log BH-02 points. From the analytical results obtained a decrease of 1.254 meters. While the PLAXIS 2D modeling uses a medium mesh that has been combined with a PVD of 1.268 meters. This means that the results of the settlement by modeling using PLAXIS 2D are closer to the SP-02 settlement plate data of 1.270 meters. The settlement uses PLAXIS 2D with a coarse mesh of 1,266 meters and a fine mesh of 1,282 meters. While modeling using preloading only obtained a decrease of 0.340 meters. It can be concluded that the results of modeling using PLAXIS 2D in using medium mesh that has been combined with PVD are relatively closer to settlement data in the field with a percentage difference of 0.142% settlement plate SP-02 settlement.